A PRAGMATIC CLASSIFICATION OF ILLOCUTIONARY ACTS IN ZOHRAN MAMDANI’S VICTORY SPEECH - Alika Larasati Legowo; Naya Amelia Cahya Putri; Cecep Agus (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The purpose of this study is to identify and categorize the many forms and purposes of illocutionary speech acts in Zohran Mamdani's victory speech. As a youthful politician from a minority group, Mamdani's discourse adds a fresh dimension to progressive political communication. This study uses a descriptive qualitative method with a pragmatic approach. The data were extracted from the transcript of Zohran Mamdani's victory speech and evaluated using Searle's speech act classification theory. The study identified five categories of illocutionary acts: assertive, directive, commissive, expressive, and declarative. Assertive acts dominate the utterances as a strategy of reinforcing identification and establishing political reality. The study indicates that the employment of illocutionary force in this speech is a strategic tool for converting electoral triumph into collective political agency for the working class. The linguistic methods used were successful in creating an inclusive narrative that challenges the existing quo while boosting minority leaders' legitimacy in the public domain.